Implementation of Dola Artificial Intelligence as a Learning Tool to Improve Students’ English Speaking Skills - Isabella, Putri; Ferdiyanto, Feri; Zainuddin, Zainuddin (Journal of English Language and Education, 2026)
In the era of globalization, English speaking skills are essential for young learners to communicate effectively and access broader knowledge resources. However, in non-formal English courses, speaking practice opportunities are often scarce, resulting in low confidence, mispronunciation, and minimal vocabulary mastery, and few studies have examined the use of AI-based tools in such settings for elementary students. This study aims to investigate the implementation of DOLA AI in improving students' speaking skills at Tekume English Course Semampir Kraksaan. A qualitative descriptive case study was employed, involving fifteen students and one tutor, with data collected through observation, interviews, documentation, and questionnaires. The findings indicate that DOLA AI created an interactive and supportive learning environment, increased students' motivation and participation, and improved pronunciation, fluency, vocabulary, and confidence. It can be concluded that DOLA AI is an effective tool for enhancing elementary students' speaking competence in a non-formal context.